Cognitive Performance and Locomotor Adaptation in Persons With Anterior Cruciate Ligament Reconstruction. (June 2018) - Stone, Amanda E.; Roper, Jaimie A.; Herman, Daniel C.; Hass, Chris J.
Background . Persons with anterior cruciate ligament reconstruction (ACLR) show deficits in gait and neuromuscular control following rehabilitation. This altered behavior extends to locomotor adaptation and learning, however the contributing factors to this observed behavior have yet to be investigated. Objective . The purpose of this study was to assess differences in locomotor adaptation and learning between ACLR and controls, and identify underlying contributors to motor adaptation in these individuals. Methods . Twenty ACLR individuals and 20 healthy controls (CON) agreed to participate in this study. Participants performed four cognitive and dexterity tasks (local version of Trail Making Test, reaction time test, electronic pursuit rotor test, and the Purdue pegboard). Three-dimensional kinematics were also collected while participants walked on a split-belt treadmill. Results . ACLR individuals completed the local versions of Trails A and Trails B significantly faster than CON. During split-belt walking, ACLR individuals demonstrated smaller step length asymmetry during EARLY and LATE adaptation, smaller double support asymmetry during MID adaptation, and larger stance time asymmetry during DE-ADAPT compared with CON. Conclusions . ACLR individuals performed better during tasks that required visual attention and task switching and were less perturbed during split-belt walking compared to controls. Persons with ACLR may use different strategies than controls, cognitive or otherwise, to adapt locomotor patterns.